Pengaruh ukuran bulir zeolit terhadap kadar bioetanol dari tanaman tebu (Saccharum Officinarum) (Effect of zeolite grain size on bioethanol levels from sugarcane (Saccharum Officinarum)) - Ornella Frita; - Ratnawulan; - Gusnedi (PILLAR OF PHYSICS, 2015)
Zeolite is an adsorbent is used to improve the purity of bioethanol from sugar cane. Bioethanol produced  by the sugar cane using of the fermentation procces and distillation procces obtained the highest levels of only 90%, and with repeated distillation the content of bioethanol does not increase. It necessary for an alternative method immersion of zeolite into bioethanol for 24 hours. Zeolite with varying size  of 50 mesh, 80 mesh, 100 mesh, 200 mesh was into the bioethanol content of 90% and produced bioethanol content of  91,3%, 92%, 93,3% and 94%. Bioethanol content 94% is also done the same thing and produced of 95%, 95%, 95,5%, 95,5%. In general, an increase in the levels of bioethanol in the size grains of zeolit used.